Elevated [CO2] raises the temperature optimum of photosynthesis and thus promotes net photosynthesis of winter wheat and rice. Issue 4 (25th August 2022) - Lv, Chunhua; Huang, Yao; Sun, Wenjuan; Yu, Lingfei; Hu, Zhenghua
Abstract: Atmospheric CO2 concentration ([CO2 ]) has increased by 49% since the pre‐industrial era, and this increase will continue. Photosynthesis has long been recognized as one of the most temperature‐sensitive processes, while far less is known about how elevated [CO2 ] (e[CO2 ]) affect crop photosynthesis response to short‐term temperature increase. To reveal the effect, we measured gas exchange of winter wheat and rice with various leaf temperatures ( T L ) under different [CO2 ] conditions (ambient, +120 μmol mol −1 in wheat, +160 μmol mol −1 in rice, and +200 μmol mol −1 in both) using open‐top chamber facility. Analysis of the measurements showed that e[CO2 ] generally increased net photosynthesis ( P n ) by 10–40% across various T L at different developmental stages. The temperature sensitivity of P n was negatively correlated with T L . Elevated [CO2 ] raised the temperature optimum ( T opt ) of P n by 1.8–5.6°C for wheat and 2.2–4.8°C for rice, resulting in a wider range of T L that can promote P n . The responses of stomatal conductance, the maximum rate of carboxylation and the ratio of intercellular to growth environment [CO2 ] to T opt are not only crop‐specific but also stage‐dependent. Furthermore, there is a divergence in the relationships between photosynthetic parameters for wheat and rice at T opt . We conclude that e[CO2 ] raises T opt of leaf photosynthesis and thus promotes P n of winter wheat and rice in a humid subtropical climate. Further research on the coordination of leaf hydraulic and photosynthetic parameters in upland wheat and irrigated rice, as well as their response to e[CO2 ] should be made in the context of climate change.